The Identification of Polyphenolic Compounds and the Determination of Antioxidant Activity in Extracts and Infusions of Peppermint, Lemon Balm and Lavender - Urszula Sadowska; Ruth Armenta Villavicencio; Kinga Dziadek; Joanna Skoczylas; Szymon Kamil Sadowski; Aneta Kopeć (Applied Sciences, 2024)
Bioactive compounds are molecules that may have therapeutic potential with influence on oxidative stress, pro-inflammatory state and metabolic disorders. Herbs are recognized as a significant source of natural antioxidants. The aim of this study was to determine the antioxidant properties of peppermint (Mentha piperita L.), lemon balm (Melissa officinalis L.) and lavender (Lavandula angustifolia Mill.). Fresh plant materials were harvested and obtained from the Experimental Station of Agriculture University in Kraków, Poland. Proximate analysis (protein, fat, ash and dry matter) was performed on herbs. Total polyphenol content and polyphenol profile antioxidant activity (ABTS and FRAP methods) were measured in an extract prepared with deionized distilled hot water (infusion), 70% methanol or 70% methanol acidified with formic acid. It was found that the water extract of peppermint had the highest polyphenol content and antioxidant activity measured by the FRAP method. The highest antioxidant activity measured with the ABTS method was in methanolic lemon balm extract. The highest amount of total phenolic compound was determined in the water extract of peppermint. The water and acidified methanol extract of peppermint contained a higher amount of naringin, rutin, hesperidin and rosmarinic acid. Evaluated plants can be used as natural antioxidants instead of synthetic antioxidants in the food and pharmaceutical industries.